PECULIARITIES OF SALT TOLERANCE OF SUGAR SORGHUM (SORGHUM SACCHARATUM (L.) PERS.) VARIETIES (Experimental biology, 2021)
This article is devoted to the study of the toxic effect of NaCl on sorghum plants, as one of the environmental stress factors and the release of stress-active substance (proline), as one of sensitive response of plant to salinity. The results of the study showed that the Russian variety Larets and the Kazakh variety Kazakhstan-20 germinate and grow well on saline soils. In a comparative study of sorghum varieties, a high degree of salt tolerance was determined in varieties Larets and Kazakhstan-20 and a high sensitivity to salinity of the Chinese variety Kulzha. It was found that the salt-sensitive cultivar Kulzha had a high level of synthesis of stress-active substances. The research results showed that the synthesis of proline, as one of the indicators of resistance to salinity, is not directly related to the accumulation of aboveground biomass. It was noticed that as the concentration of salt in the soil in the variety Kazakhstan-20 increased, the aboveground biomass was high for some time (from 78.22 to 69.82) and the amount of proline was also high for some time, but due to an increase in the concentration of salt in the soil, the content of proline significantly decreased. On the other hand, in the Larets cultivar, on the contrary, with the accumulation of biomass, the synthesis of proline immediately decreased. In the cultivar Kulzha, which is most sensitive to salinity, as the biomass of the stem decreased, the synthesis of proline, on the contrary, increased. This indicates that proline synthesis is not associated with a stress tolerance response in a crop such as sorghum.
Keywords: NaCl, salinization, proline, sorghum, stress, chaperone.